Investigation of the Levels of Belonging to the School of Individuals Taking a University Education - Türkçapar, Ünal (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: This study aims to determine how the level of belonging to the school is shaped by individuals studying in different faculties of Kyrgyzstan Turkey Manas University. Material and Methods: Scanning method was used in the research. This research is descriptive and inferential study. The study group of this research consists of 114 female and 97 male participants studying in the Departments of Veterinary, Communication, and Sports Sciences of Kyrgyzstan Turkey Manas University in the 2020-2021 academic year. The study was based on voluntary participation criteria. Personal information form prepared by the researcher and The Scale of Belonging to School were used to collect data. The personal information form consists of questions such as gender, department of education, mother’s education level, father’s education level, hobbies you enjoy, social facility adequacy and monthly income level. In addition, in order to determine the participants sense of belonging to the school; A 5-point Likert-type "Sense of Belonging to School Scale" consisting of 18 items developed by Goodenow (1993) and adapted into Turkish by Sarı (2015) was used. The obtained data were evaluated in computer environment using SPSS 26.0 statistical program. Results: It was concluded that there was no significant difference in the variables of gender, department, mother's education level, father's education level and the hobbies you enjoy, but there was a significant difference in the variables of monthly income and social facility adequacy. Conclusion: It has been concluded that the social facility adequacy and monthly income level variables are the determining factors in shaping the level of belonging to the school of university students.